Solvothermal synthesis of flower-like CoS hollow microspheres with excellent microwave absorption properties. Issue 102 (21st October 2016) - Huang, Tingyuan; He, Man; Zhou, Yuming; Li, Shiwei; Ding, Binbin; Pan, Wenlu; Huang, Shuang; Tong, Yuan
Abstract : In this study, flower-like CoS hollow spheres (CHSs), synthesized via a facile solvothermal method in the presence of CTAB, were initially investigated as microwave absorbers. Abstract : In this study, flower-like CoS hollow spheres (CHSs), synthesized via a facile solvothermal method in the presence of CTAB, were initially investigated as microwave absorbers. It was found that such microstructure was significantly different from CoS nanoparticles (CoS NPs) prepared without introducing CTAB under similar preparation conditions. Moreover, with a low filler loading of 20 wt%, CHSs based composite could reach an optimal reflection loss of −43.6 dB at 15.6 GHz, and exhibit an effective absorption bandwidth (below −10 dB) of 4.6 GHz (13.2–17.8 GHz) at the thin thickness of 2.0 mm. Furthermore, through adjusting the thickness from 2.0 to 5.0 mm, an effective absorption bandwidth of 13.2 GHz could be monitored in the frequency range of 4.8–18.0 GHz. The results indicate that the novel CHSs are intriguing microwave absorbers with the advantages of strong absorption, broad bandwidth, light weight and thin thickness, which is attributed to the unique nanoarchitecture, extra void space, and high dielectric loss.